ITS for freight logistics - Kawashima, Hironao (IET transportation series ;, 2022)
The use of ICT and ITS (intelligent transport systems) have supported the developments of more rapid, more reliable and more precisely timed strategies for freight transport. This book reviews recent developments in the field of ITS for freight logistics.